Time-Frequency Analysis and Its Applications to Multimedia Signals. (6th March 2011) - Stanković Stanković, Srdjan Srdjan; Krishnan Krishnan, Sridhar Sridhar; Mobasseri Mobasseri, Bijan Bijan; Zhang Zhang, Yimin Yimin
Abstract :